2010
DOI: 10.1016/j.seppur.2009.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cyanobacterial cells removal and lysis by ultrafiltration

Abstract: The aim of this study was to evaluate the ultrafiltration (UF) performance for removing Microcystis aeruginosa cells under different growth ages (1, 2, 3 and 4 months old). Special attention was given to cell damaging and subsequent release of microcystins to permeate. Experiments were performed with a hollow-fibre cellulose acetate membrane (100 kDa). UF achieved an absolute removal of M. aeruginosa single cells, producing chlorophyll-a free water and with a turbidity below 0.1 NTU. Cell lysis occurred at all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 26 publications
2
29
1
3
Order By: Relevance
“…Figure 4 shows the occurrence of cell lysis in both cultures, with a stronger impact in the older culture and at the end of the filtration cycle. Chlorophyll-a concentration is not shown but was less sensitive to cell lysis than the intra-microcystins concentration (Campinas & Rosa, 2010a). On the other hand, Figure 5 reveals a cycle-averaged rejection of total microcystins of 60% with the 2 months old culture and of 80% with the 4 months old cells, which indicates the importance of the adsorption phenomenon for this older culture.…”
Section: Cell Lysismentioning
confidence: 86%
See 2 more Smart Citations
“…Figure 4 shows the occurrence of cell lysis in both cultures, with a stronger impact in the older culture and at the end of the filtration cycle. Chlorophyll-a concentration is not shown but was less sensitive to cell lysis than the intra-microcystins concentration (Campinas & Rosa, 2010a). On the other hand, Figure 5 reveals a cycle-averaged rejection of total microcystins of 60% with the 2 months old culture and of 80% with the 4 months old cells, which indicates the importance of the adsorption phenomenon for this older culture.…”
Section: Cell Lysismentioning
confidence: 86%
“…aeruginosa culture (Pasteur Culture Collection, PCC 7820) was grown in the laboratory, in BG11 medium, at 23-24ºC, under a light regimen of 12 h fluorescent light, 12 h dark. Depending on the experiment, cultures were harvested at different growth ages, namely 1, 2-3 and 4 months, corresponding to exponential phase, late exponential phase and stationary phase, respectively (Campinas & Rosa, 2010a), and used to simulate cyanobacterial blooms. Cyanotoxins are produced at all stages of cyanobacterial growth and usually stay inside the cell (intracellular) until age or stress-driven cell lysis causes their release into the water (extracellular) (Sivonen & Jones, 1999).…”
Section: Cyanobacterial Cells and Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the chlorophyll-a content in raw water was about 4-5.5 μg·L − 1 , and the average content was 4.67 ± 0.39 μg·L −1 during the experiment. The chlorophyll-a was almost completely removed and only a minute trace could be detected in the effluent of UF and PAC/UF processes, because of the bigger size of M. aeruginosa cells (3-7 μm) as compared with the pore size of membrane (0.01 μm) [24]. The results indicated that both PAC/UF and UF process could achieve almost complete removal of algal cells for the sieving function of UF membrane.…”
Section: Algal Cell Removalmentioning
confidence: 93%
“…For MF/UF systems, the range in algal cell removal efficiencies was also summarized from pilot and full-scale SWRO plant studies [38,[43][44][45][46]. Uniform probability distributions were used in the pMFA model for MF/UF systems considering the small number of reported observations from the literature ( Table 2).…”
Section: Intracellular and Dissolved Toxin Removal Efficienciesmentioning
confidence: 99%